COMPETENCY OF CLASS TEACHERS IN THE IMPLEMENTATION OF GUIDELINES DEMANDS IN EXTRAORDINARY ELEMENTARY SCHOOLS - Triani, Nani; Suherman, Uman; Nurihsan, Juntika (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
This research departs from the fact that learning with nuances of guidance in extraordinary elementary schools has not been done much so that the purpose of this study is to find out data about these matters. This study uses a quantitative approach with descriptive methods with 34 teachers as respondents. Areas that become indicators are mastery of identification and assessment of students, the ability of teaching theories & principles of educational learning, and the development of learning tools with instructional learning principles. The results showed that in the mastery of identification and assessment, most of the students were in the less competent category, a few were competent, and the rest were less skilled. The ability to master learning theory and educational learning principles shows that most of them are in the competent category and the rest are in the weak and incompetent category, while the ability to develop learning tools following nuanced learning guidance is mostly in the category of resting competent very competent, incompetent and less competent. Based on the data obtained in the research results, it shows that the competence of elementary school class teachers is extraordinary in carrying out guided learning and shows excellent competence so that it still requires development assistance using various techniques, methods, strategies, and appropriate approaches.